A new species of planthopper in the genus Anchimothon (Hemiptera: Auchenorrhyncha: Derbidae) on palms from Costa Rica - Bahder, Brian W.; Barrantes, Edwin A.; Echavarria, Marco A. Zumbado; Helmick, Ericka E.; Bartlett, Charles R. (Zootaxa, 2022)
Anchimothon is a small genus of derbid planthoppers known from Mesoamerica and northern South America. Recent survey efforts in the Caribbean basin have documented many new taxa of fulgoroids from palms. During this survey, a novel taxon identified as Anchimothon was collected from palm seedlings at La Selva Biological Station in Costa Rica. Here, the novel taxon is described as A. myriei sp. n. with molecular data for the cytochrome c oxidase subunit I (COI) and18S rRNA providing support for placement of the new species in Anchimothon. An updated key is provided for the current species of Anchimothon.